Effect of Stitching Patterns on Tensile Strength of Kenaf Woven Fabric Composites - Yaakob, Mohd Yuhazri; Husin, Mohd Amirhafizan; Abdullah, Abu; Mohamed, Kamarul Amir; Khim, Ang Siew; Chuok Fang, Michelle Lye; Sihombing, Haeryip (International Journal of Integrated Engineering, 2019)
In the past years, the natural fibre had attracted much attention by many researchers as an alternative fibre to replace synthetic fibre composite materials today. An experimental study was conducted to explore the effect of stitching on woven kenaf fabric. The hand lay-up and vacuum bagging technique were used. The composites were made of woven kenaf fabric as a reinforcement and epoxy resin as a matrix. The composites were made in different patterns of stitches that split into two categories which were basic pattern that was stitched by the single cross which includes Vertical, Horizontal, Tilt 30 ÌŠ and Tilt 60 ÌŠ. The other one was complex pattern, stitched by the double cross which includes Box, Tilt 45 ÌŠ /90 ÌŠ, Tilt 30 ÌŠ/30 ÌŠ and Tilt 60 ÌŠ/60 ÌŠ. It was found that the increasing specific strength for single stitch composite of the V, T60, and T30 patterns were 14.51 %, 1.49 % and 0.64 % respectively, compared to the unstitched composite. The specific strength produced by V stitch which was about 9.53 MPa/g,was higher than other stitch patterns. The results also showed that the specific strength for all the double stitch patterns were gradually increased compared to the unstitched ones. T60/60 exhibited the highest specific strength which increased about 53.17 % compared to the unstitched composite. The evidence from this study suggested that the double stitch composite gave better performance in specific strength, while stitching patterns and stitching angle gave significant effect to the performance of woven stitch kenaf composite compared to the unstitched ones. Implications of the results and future research direction were also presented.